2008
DOI: 10.1075/lald.47.12lis
|View full text |Cite
|
Sign up to set email alerts
|

Associating meaning to form in advanced L2 speakers: An investigation into the acquisition of the English present simple and present progressive

Abstract: This paper investigates the L2 acquisition of the distributional and interpretational properties of the English present simple (e.g., She works at home) and present progressive (e.g., She is working at home). To test whether advanced L2 learners are successful in assigning target-like meanings to these forms, sixteen advanced L1 French-L2 English and thirteen L1 English informants participated in two oral tasks and a written gap-fill task. Results indicate that these L2 speakers use both forms productively, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In line with the laboratory findings, the classroom experiment showed that intermediate English‐Spanish and English monolinguals relied more on adverbs than verbs to resolve tense conflicts between cues, but Spanish monolinguals preferred verbal to adverbial cues. Although these findings could be due to a general L2 trend to rely on lexical cues, the Latin data and the numerous studies showing L1 influence on the comprehension of L2 tense/aspect (e.g., Hawkins et al, 2008; Liszka, 2009; Roberts & Liszka, 2010) lead us to conclude that cues learned early in the laboratory or the L1 block the acquisition of later experienced L2 cues. Our current work comparing learners of L2 Spanish whose L1 is morphologically null (Chinese), poor (English), or rich (e.g., Rumanian) will help us strengthen our argument.…”
Section: Discussionmentioning
confidence: 74%
“…In line with the laboratory findings, the classroom experiment showed that intermediate English‐Spanish and English monolinguals relied more on adverbs than verbs to resolve tense conflicts between cues, but Spanish monolinguals preferred verbal to adverbial cues. Although these findings could be due to a general L2 trend to rely on lexical cues, the Latin data and the numerous studies showing L1 influence on the comprehension of L2 tense/aspect (e.g., Hawkins et al, 2008; Liszka, 2009; Roberts & Liszka, 2010) lead us to conclude that cues learned early in the laboratory or the L1 block the acquisition of later experienced L2 cues. Our current work comparing learners of L2 Spanish whose L1 is morphologically null (Chinese), poor (English), or rich (e.g., Rumanian) will help us strengthen our argument.…”
Section: Discussionmentioning
confidence: 74%
“…In Liszka (2009), the findings from a larger number of participants (n ¼ 16) showed very high accuracy scores on assigning target-like meanings to present simple forms (100%) and present progressive forms (92.7%) in the oral description task. In the video clip description tasks, whereas the accuracy scores for the present simple forms remained high (94.4%), the use of present progressive forms dropped to 52.8% of obligatory contexts which may not simply be a task e¤ect due the real-time processing pressure because a similar pattern was obtained for the contextualized dialogue task (94.2% for simple present and 54.8% for present progressive).…”
Section: Tense and Aspect In L2 Englishmentioning
confidence: 92%
“…Moreover, we would like to suggest that Liszka's (2009Liszka's ( , 2015 findings must be interpreted with caution, given the coding procedure used in this study. For example, in the video clip description task, the use of the Present Progressive was coded as appropriate with thematic verbs, and the production of the Present Simple with thematic verbs was only coded as appropriate when combined with an appropriate licensing adverbial expression, such as 'then, as soon as, etc.'.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In order to test the effects of L1 transfer on real-time oral production, we asked participants to complete a modified version of the video description task from Liszka's (2009Liszka's ( , 2015 study.…”
Section: Task Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation